2017
DOI: 10.1167/iovs.16-21208
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvasculature and Visual Acuity in Eyes With Branch Retinal Vein Occlusion: Imaging Analysis by Optical Coherence Tomography Angiography

Abstract: Preservation of the deep retinal vasculature is crucial for better visual function in BRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 58 publications
7
65
2
Order By: Relevance
“…Our results are consistent with previous studies that addressed the favorable effects of retinal perfusion in the DCP on visual acuity in patients with RVO. 18 Therefore, strategies that preserve retinal perfusion especially in the DCP should be explored to improve visual outcomes after RVO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with previous studies that addressed the favorable effects of retinal perfusion in the DCP on visual acuity in patients with RVO. 18 Therefore, strategies that preserve retinal perfusion especially in the DCP should be explored to improve visual outcomes after RVO.…”
Section: Discussionmentioning
confidence: 99%
“…The visual improvement after treatment of macular edema significantly correlates with better retinal perfusion and less retinal ischemia in patients with RVO. [16][17][18][19][20][21] Therefore, the effects of repeated anti-VEGF therapy to the retinal perfusion should be investigated for a better longterm management of RVO. Optical coherence tomography angiography (OCTA) enables noninvasive visualization of different retinal layers, such as the superficial and deep retinal capillaries by segmentation of each layer.…”
mentioning
confidence: 99%
“…FAZ enlargement is related to worse vision in diabetic retinopathy and retinal vein occlusions. 26,27 Capillary density of both plexuses is correlated to visual loss in diabetic retinopathy, 28 branch retinal vein occlusion, 29,30 and idiopathic macular telangiectasia type 1 (MacTel1). 31 In addition, several investigators have shown that decreased perfusion is more frequent in the deep than superficial plexus, in central or branch vein occlusion, 32-34 diabetic retinopathy, 35 and MacTel1.…”
Section: Discussionmentioning
confidence: 99%
“…36 In resolved branch retinal vein occlusion, deep plexus nonperfusion has recently been identified as a more critical determinant of BCVA than superficial plexus nonperfusion. 30 Noticeably, vascular and structural alterations of radiation maculopathy present similarities with diabetic retinopathy, retinal vein occlusion, or MacTel1, including macular edema, microaneurysms, and capillary nonperfusion. In the present study, OCTA revealed that the deep plexus of irradiated eyes was more severely altered than the superficial plexus.…”
Section: Discussionmentioning
confidence: 99%
“…Using this novel, non-invasive, dyeless technology, it was possible to recognize the presence of the signs of RVO at the level of superficial capillary plexus (SCP) and deep capillary plexus (DCP), as non-perfusion areas, disruption of perifoveal arcade, cysts, and dilation of macular capillaries [1]. In particular, OCTA allowed a direct visualization of DCP, not visible on fluorescein angiography, and particularly involved in RVO [2]. Recently, the OCTA analysis of vessel density (VD) has been correlated with a recurrence of disease and number of intravitreal anti-VEGF injections [3].…”
Section: Introductionmentioning
confidence: 99%